Late Lung Metastasis in a Patient with a Clear Cell Chondrosarcoma: An Indication for a Life-Long Follow-Up?. (2nd December 2021) - West, Paulien; Jacobs, Celine; Saerens, Michael; Creytens, David; Sys, Gwen; Lapeire, Lore
Abstract : Background . Clear cell chondrosarcoma (CCCS) is a rare subtype of chondrosarcoma and comprises between 1.6% and 2.5% of all chondrosarcoma. They are known to be chemo- and radiotherapy resistant; surgical resection is therefore the therapy of choice. Methods . We present a 63-year-old woman with a progressive lung nodule 20 years after initial diagnosis and treatment of a clear cell chondrosarcoma of the right os naviculare. Results . On serial CT scans of the chest, an asymptomatic, slowly growing nodule in the left upper lung lobe was detected. CT-guided transthoracic biopsy of this nodule confirmed the diagnosis of a chondrosarcoma lung metastasis. Video-assisted thoracoscopic wedge resection was performed with complete removal of the nodule. The patient recovered well from surgery and remains in good health during further follow-up. Conclusion . Given the tendency of clear cell chondrosarcoma to recur and metastasize after extended periods of time, a long-term, possibly life-long follow-up and clinical surveillance is advisable in these patients.